The Role of Metropolitan Centers in the Development of Regions in the Light of Programmes of Development of Regions, on the Example of the Malopolskie, Mazowieckie and Dolnoslaskie Voivodships - Kudłacz, Michał (Journal of Public Governance, 2010)
The main hypothesis of the article is that there are natural interactions between metropolitan centers and their surrounding areas (regions). In the present study, focused on the following three examples: Krakow and the Malopolska region, Warsaw and the surrounding Mazowieckie Voivodship, and Wroclaw with the Dolnoslaskie Voivodship, the author analyzes if these interactions are taken into consideration in the development of policies at the local (metropolitan) and the regional level (region surrounding the core city). A lack of compatibility of these policies has a negative impact on the development of the region. The impact of large cities on the development of their environment would be greater if it was encouraged by politicians and their interventions.The author attempts to determine how local governments can influence the impact of metropolitan cities on their surrounding areas, and what use can be made of their natural interactions. Nowadays, local and regional authorities are often accused of creating strategies without prior consultation with the interested parties. Combining the efforts of local and regional authorities would ensure a coherent socio-economic development and could be beneficial for both levels of self-government.